Bronchoscopic suspect of Herpesvirus infection in critically ill COVID-19 patients: two case reports and brief literature review - Deana, Cristian; Vetrugno, Luigi; Stefani, Francesca; Bassi, Flavio (Acta Biomedica Atenei Parmensis, 2022)
Herpesviridae infection in COVID-19 patients has been reported, particularly muco-cutaneous lesions. Little is known about Herpesviridae lung infection in critically ill COVID-19 patients. Typical scattered lesions seen through fiberoptic bronchoscopy in these patients should raise the question as to whether to start empirically acyclovir treatment while a Herpesviridae diagnostics result becomes available.